The Gynecologic Health Consequences of Chlamydia trachomatis Infection in Military Servicewomen - Nadeau, Christine; Fujii, Dennis; Lentscher, Jessica; Haney, Amanda; Burney, Richard O. (Seminars in Reproductive Medicine, 2018)
Chlamydia trachomatis is the most common sexually transmitted bacterial infection in the United States. Within the U.S. military, the age- and race-adjusted chlamydia infection rates among female service members are consistently higher than civilian rates, with a 20% annual acquisition rate among young active-duty women. The sequelae of chlamydia disproportionately impact women in terms of severity and cost. Untreated chlamydia progresses to pelvic inflammatory disease in 40% of cases, and is a leading cause of fallopian tube damage and pelvic adhesive disease resulting in ectopic pregnancy, tubal infertility, and acute and chronic pelvic pain. Tubal infertility is among the leading indications for in vitro fertilization (IVF) nationally and rates among couples undergoing IVF at military treatment centers are double the national average. Collectively, chlamydia infection represents a significant resource burden to the military health care system and, in view of the serious gynecologic health sequelae, a significant threat to the readiness of servicewomen. In this review, we discuss the gynecologic impact of chlamydia infection within the military, the critical gaps for research funding, and opportunities for intervention.
Keywords: chlamydia; salpingitis; tubal; infertility; ectopic; military